A note on strong (skew) η-Lie products preserving maps on some algebras. Issue 5 (4th May 2019) - Taghavi, Ali; Kolivand, Farzaneh; Tavakoli, Ensiyeh
ABSTRACT: LetA be an arbitrary unital *-algebra over the real or complex fieldF, and letη ∈ F withη ≠ 1 . Assume thatΦ : A ⟶ A is a map. It is shown that, ifΦ satisfiesΦ ( A ) Φ ( P ) - η Φ ( P ) Φ ( A ) ∗ = A P - η P A ∗, for eachA ∈ A and projectionP ∈